VISEGRAD MEETS VISEGRAD: THE VISEGRAD FOUR AND THE WESTERN BALKANS SIX - Ciderova, Denisa; Kovacevic, Dubravka (European Scientific Journal, ESJ, 2015)
Enlargements of the European Union (EU) over the recent decade have not just expanded its territory or increased the headcount of its Single Market; by almost doubling the number of its Member States (MSs) the EU faces multifaceted implications beyond any doubt. Having been challenged by multiple transformation, the Central and East European Countries (CEECs) assumed their rights just like obligations associated with EU membership upon completion of transitional periods intended to allow for as much a smooth integration process as possible. Accession to the EU reinforced their prestige internationally to the extent of intensity of their participation (i.e. in terms of “mere“ EU membership, or even complemented by a single currency in the Euro Area, and/or single external EU border in the Schengen Area). Gradually, they aspire to maximise their inward financial flow from the common EU budget while simultaneously “catching up“ with the “Western“ degree of political and economic development; post- Cold-war democracies increasingly engage in institutional representation, coalition building and pursuit of own interests amidst the EU arena, too. In this respect we streamline our focus to the Western Balkans and the shaping concept of the so-called Western Balkans Six with the aim to hint prospects of cooperation inspired by the Visegrad Group alias the Visegrad Four (V4).